The Role of Tetrazinyl Radical Ligands in Lanthanide Metallocene Single-Molecule Magnets - Mavragani, Niki (Université d'Ottawa | University of Ottawa, 2025)
Being at the forefront of new technological advancements in quantum information processing and spintronics, single-molecule magnets (SMMs) have greatly benefited from the incorporation of lanthanide (Ln) ions. Although mononuclear organometallic Ln-based SMMs have been the clear frontrunners in achieving high blocking temperatures and large energy barriers, the weak Ln···Ln magnetic interactions hinder the magnetic performance of polynuclear Ln-based SMMs. To this end, radical ligands with diffuse electron density can promote strong magnetic interactions with the Ln ions and potentially lead to strongly coupled, high-performing SMMs. The present dissertation focuses on exploring s-tetrazines as bridging ligands in lanthanocene complexes with a close emphasis on their magnetic properties. In pursuit of tetrazinyl-bridged lanthanocene SMMs, the combination of highly delocalized 1,2,4,5-tetrazinyl radical anion (tz•–) with lanthanide metallocenes led to the isolation of a family of radical-bridged dinuclear lanthanocene complexes: [(Cp*2Ln)2(tz•–)(THF)2](BPh4) (Ln = Gd (1-Gd), Tb (1-Tb) and Dy (1-Dy); Cp* = pentamethylcyclopentadienyl; THF = tetrahydrofuran). Magnetic measurements and computational studies confirmed the very strong magnetic exchange coupling, which was found to be JGd–rad = –7.2 cm-1 for 1-Gd. Combined with the highly anisotropic TbIII and DyIII ions in 1-Tb and 1-Dy, the strong Ln-rad magnetic exchange coupling led to zero-field SMM behaviour and waist-restricted magnetic hysteresis loops. These dinuclear complexes serve as ideal models for understanding the magnetic interactions promoted by tetrazinyl radical bridges with 4f elements. Taking advantage of the Cp* ancillary ligands and the steric effects imposed by their bulkiness, the chelate 3,6-bis(3,5-dimethyl-pyrazolyl)-1,2,4,5-tetrazine (bpytz) was incorporated into a series of radical-bridged Ln2 metallocenes: [(Cp*2LnIII)2(bpytz•−)](BPh4) (where Ln = Gd (2-Gd), Tb (2-Tb), Dy (2-Dy), Y (2-Y) and Er (2-Er)). Notably, it was found that compared to the cis fashion, the trans coordination of the bpytz•− enabled one of the strongest exchange couplings observed in radical-bridged Ln metallocene complexes; JGd–rad = –14.0 cm-1. The strong Ln-rad exchange coupling was further verified by high-frequency EPR (HF-EPR) spectroscopy and computational studies. In-depth analysis of the magnetic properties for 2-Tb, 2-Dy and 2-Er revealed slow magnetic relaxation but different magnetic performance, which was attributed to the intricate electronic differences of the individual LnIII ions. Altering the electron distribution of the tetrazine ring by introducing electron-donating or withdrawing substituent groups at the 3- and 6-positions of the tetrazine ring affects the strength of the Ln-rad magnetic coupling. To elucidate the true influence of the substitution, a series of radical-bridged Ln2 metallocene complexes featuring the 3,6-dimethyl-1,2,4,5-tetrazine (dmtz) and the 3,6-dimethoxy-1,2,4,5-tetrazine (dmeotz) were synthesized: [(Cp*2Ln)2(dmtz•–)(THF)2](BPh4)·THF (Ln = Gd (3-Gd) and Dy (3-Dy)) and [(Cp*2Ln)2(dmeotz•–)(THF)](BPh4) (Ln = Gd (4-Gd) and Dy (4-Dy)). Cyclic voltammetry, UV-Vis absorption spectroscopy, SQUID magnetometry, as well as theoretical calculations were combined to underline the trends observed in this study, while comparisons to the unsubstituted 1,2,4,5-tetrazine (tz) and the 3,6-dichloro-1,2,4,5-tetrazine (dctz) were made. Both 3-Dy and 4-Dy exhibit slow magnetic relaxation at zero field, while a coercive field of ~5000 Oe was observed for 3-Dy. Further exploration of the incorporation of tetrazinyl radical bridges into lanthanide metallocene complexes led to tetranuclear radical-bridged complexes: [(Cp*2Ln)4(tz•−)4]⋅3(C6H6) (Ln = Gd (5-Gd), Tb (5-Tb) and Dy (5-Dy)). The very strong JGd–rad1 = –12.0 cm-1 and JGd–rad2 = −7.5 cm-1 promoted by the tz•– bridges led to 5-Ln acting as a molecular entity, with a highly sought-after “giant-spin”, rather than weakly coupled individual spin centres. Both 5-Tb and 5-Dy exhibit slow magnetic relaxation at zero field. However, the electronic differences of the TbIII and DyIII ions resulted in waist-restricted hysteresis loops in 5-Tb, while in 5-Dy, the hysteresis loops were open with a large coercive field of 30 kOe. The giant coercivity obtained for 5-Dy provides a glimpse into the potential of polynuclear radical-bridged Ln SMMs to access systems with enhanced magnetic hardness, a critical aspect when envisioning next-generation storage devices. A combination of strictly anhydrous and inert synthetic conditions, strong reducing agents, and non-acidic solvents, as well as blocking the accessibility of the nitrogen atoms by coordinating them to LnIII ions, allowed for the stabilization of the first structurally and physically characterized complexes bearing a dianionic tetrazine species: [(Cp*2Ln)2(tz2−)(THF)2]·2THF (Ln = Gd (6-Gd) and Y (6-Y)). Detailed structural analysis, physical characterization, ab initio calculations, as well as comparison to the radical-bridged complexes 1-Gd and 1-Y, support that the tz2– ligand is a closed-shell planar dianion with unique structural features vastly different from those of the dihydro (H2tz), neutral (tz), or radical (tz•−) species. Employing radical ligands that can store unpaired electrons might be the key to promote strong magnetic interactions in polynuclear Ln SMMs. Incorporation of both radical and dianionic tetrazine bridges in the same molecular structure allowed for the isolation of the first examples of hexanuclear radical-bridged Ln metallocene complexes: [Cp*10Ln6(dmeotz2–)(dmeotz•–)4(THF)4](BPh4)2 (Ln = Gd (7-Gd) and Dy (7-Dy)). In-depth analysis of the magnetic properties of 7-Gd revealed the presence of strong Ln-dmeotz•– magnetic coupling, while 7-Dy exhibited thermally-activated magnetic relaxation at zero field. To unravel the observed trends of the magnetic properties of 7-Ln, magneto-structural correlations were employed. The collective results of this dissertation provide critical insights into the role of s-tetrazinyl radicals in radical-bridged Ln SMMs.
Keywords: Single-Molecule Magnets; s-Tetrazines; Radical-Bridged Lanthanocene Complexes; Magnetic Materials; Inorganic Chemistry; Organomettalic Chemistry